Pervaporation separation of ethyl acetate-ethanol binary mixtures using polydimethylsiloxane membranes - Hasanoglu, A; Salt, Y; Keleser, S; Özkan, S; Dinçer, S (ELSEVIER SCIENCE SA, 2005)
Pervaporation separation of azeotrope forming ethyl acetate-ethanol mixtures was investigated by using a selfmade polydimethylsiloxane (PDMS) membrane. Sorption, desorption and pervaporation experiments for ethyl acetate-ethanol mixture with different concentrations were conducted at 30, 40 and 50 degreesC. The effect of process parameters such as feed concentration and temperature on flux and selectivity is discussed. Equilibrium curves are determined by vapor-liquid equilibrium calculations using Wilson equation. Data obtained by pervaporation are compared with the points determined from vapor-liquid equilibrium calculations. Experiments show that PDMS membrane is much more selective to ethyl acetate than ethanol. Increase in temperature yields higher total fluxes and lower selectivities of ethyl acetate. While the ethyl acetate concentrations increase from 20 to 94.5 wt.%, total fluxes and ethyl acetate selectivities change in the ranges of 756-8473 gr/m(2)h and 5.30-1.18, respectively. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: pervaporation; sorption; desorption; PDMS; ethanol; ethyl acetate; Energy & Fuels; Engineering